(untitled) (Bangladesh Journal of Botany, 2026)
Crocus sativus L. is a medicinal plant of considerable pharmacological interest. This study investigated the phytochemical composition and assessed the acute and subacute oral toxicity of the methanolic crude extract of C. sativus petals in Wistar rats. Phytochemical screening revealed high levels of flavonoids, tannins, and reducing compounds, suggesting strong antioxidant potential. In acute toxicity tests, the extract was non-lethal at doses up to 5000 mg/kg, with dose-dependent hyperglycemia as the main alteration, without major short-term hepatic or renal damage. In the subacute toxicity study, low doses were well tolerated and improved lipid parameters, whereas high doses induced significant metabolic disturbances, including hyperglycemia, dyslipidemia, and increased transaminase levels, indicating hepatotoxicity. In addition to hepatotoxicity, nephrotoxicity was also observed. The data of subacute toxicity show a massive increase in urea levels, jumping from 47.63 ± 2.30 mg/dl in the control group to 126.23 ± 8.53 mg/dl in the highest dose group. This is a 165% increase with a highly significant p-value, indicating severe renal distress or failure. Hematological analysis showed overall stability, except for reduced neutrophils and erythrocyte changes at higher doses. These findings suggest that the petal extract is potentially beneficial at low doses but exhibits toxicity at higher concentrations, warranting further studies to define its therapeutic margin. Bangladesh J. Bot. 55(2): 411-417, 2026 (June)